The 9th International Conference "Environmental Engineering 2014" 2014
DOI: 10.3846/enviro.2014.059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Climate Warming on Timing of Native and Non-Native Tree Species Phenology

Abstract: The aim of the study was to investigate impact of climate warming on timing of deciduous tree species spring (leaf unfolding) and autumn (leaf falling) phenology and to compare seasonal development and growing season changes of native (Quercus robur L.) and non-native (Quercus rubra L.) tree species. Long-term dataset of phenological observations from Kaunas Botanical Garden of Vytautas Magnus University (central Lithuania) were used for this study. Increased temperature was detected to be a strong driver of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In Europe, Q. rubra flowers in May (Klotz, Kühn, & Durka, 2002) and acorns are shed from September through October. More detailed observations from Lithuania revealed that leaves of Q. rubra were unfolding in the middle of May (Julian dates 124–134), with leaf fall near the end of October (Julian date 303), according to observations from the years 1980–2013 (Sujetovienė & Šveikauskaitė, 2014). Older observations from the Netherlands (1940–1959) estimate leaf unfolding at the beginning of May (Julian date 123; Kramer, 1994).…”
Section: Phenologymentioning
confidence: 97%
“…In Europe, Q. rubra flowers in May (Klotz, Kühn, & Durka, 2002) and acorns are shed from September through October. More detailed observations from Lithuania revealed that leaves of Q. rubra were unfolding in the middle of May (Julian dates 124–134), with leaf fall near the end of October (Julian date 303), according to observations from the years 1980–2013 (Sujetovienė & Šveikauskaitė, 2014). Older observations from the Netherlands (1940–1959) estimate leaf unfolding at the beginning of May (Julian date 123; Kramer, 1994).…”
Section: Phenologymentioning
confidence: 97%